2015
DOI: 10.1007/s13277-015-4216-2
|View full text |Cite
|
Sign up to set email alerts
|

SAHA, an HDAC inhibitor, overcomes erlotinib resistance in human pancreatic cancer cells by modulating E-cadherin

Abstract: Pancreatic cancer is one of the most lethal cancers and remains a major unsolved health problem. Less than 20 % of patients are surgical candidates, and the median survival for non-resected patients is approximately 3 to 4 months. Despite the existence of many conventional cancer therapies, few targeted therapies have been developed for pancreatic cancer. Combination therapy using erlotinib and gemcitabine is an approved standard chemotherapy for advanced pancreatic cancer, but it has marginal therapeutic bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…In HCC827IR cells, chidamide down-regulated the expression and activation of EGFR and MET, and mainly inhibited the RAS/MAPK pathway. A recent study showed that HDAC inhibitor SAHA activated the phosphorylation of EGFR and increased the cell sensitivity to erlotinib in pancreatic cancer 32. However, in the present study, chidamide monotherapy did not have obvious effect on signal pathway in H1975 cells, but when combined with a relatively high concentration of icotinib, the PI3K/AKT pathway was significantly inhibited, which resulted in arresting cell cycle and promoting apoptosis.…”
Section: Discussioncontrasting
confidence: 80%
“…In HCC827IR cells, chidamide down-regulated the expression and activation of EGFR and MET, and mainly inhibited the RAS/MAPK pathway. A recent study showed that HDAC inhibitor SAHA activated the phosphorylation of EGFR and increased the cell sensitivity to erlotinib in pancreatic cancer 32. However, in the present study, chidamide monotherapy did not have obvious effect on signal pathway in H1975 cells, but when combined with a relatively high concentration of icotinib, the PI3K/AKT pathway was significantly inhibited, which resulted in arresting cell cycle and promoting apoptosis.…”
Section: Discussioncontrasting
confidence: 80%
“…Some of these agents, including the pan‐HDAC inhibitors vorinostat (suberoylanilide hydroxamic acid [SAHA]) and panobinostat (LBH589), are now US Food and Drug Administration‐approved anticancer drugs . Several previous studies demonstrated that the combination of an EGFR‐TKI (eg, gefitinib or erlotinib) with an HDAC inhibitor (eg, MS‐275, SAHA, LBH589, MPT0E028, or YF454A) enhanced their effects, including the induction of apoptosis and the inhibition of growth in glioblastoma, pancreatic cancer, head and neck cancer, and lung cancer cells . However, whether the combination of osimertinib with an HDAC inhibitor exerts enhanced effects against EGFR‐mutant NSCLC cell lines that have acquired resistance to osimertinib has not been well studied and thus is the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…However, in pancreatic cancer, erlotinib is not widely used. Numerous studies have been performed in an effort to overcome erlotinib resistance in pancreatic cancer, investigating the use of inhibitors of MEK [9, 10], AKT2 [11,12], HDACs [13], and PI3K/mTOR [10,12].…”
Section: Discussionmentioning
confidence: 99%